A Phthalocyanine‐Based Glutathione‐Activated Photosensitizer with a Ferrocenyl Boron Dipyrromethene Dark Quencher for Photodynamic Therapy. Issue 10 (21st June 2019) - Shi, Wen‐Jing; Ng, Dennis K. P.; Zhao, Shirui; Lo, Pui‐Chi
Abstract: An efficient near‐infrared‐absorbing dark quencher based on ferrocenyl boron dipyrromethene (BODIPY) has been developed and used to construct a fluorescence resonance energy transfer (FRET)‐based activatable photosensitizer. This smart photosensitizer contains a zinc(II) phthalocyanine as the photosensitizing unit which is conjugated to this dark quencher through a glutathione‐cleavable disulfide linker. The photoactivities of the phthalocyanine unit are largely quenched through FRET to the BODIPY unit followed by photoinduced electron transfer from the attached ferrocenyl moiety. Upon exposure to glutathione in phosphate buffered saline and inside HT29 human colorectal adenocarcinoma cells, the fluorescence emission and singlet oxygen generation efficiency of the photosensitizer are significantly enhanced due to cleavage of the disulfide bond and detachment of the dark quencher from the photosensitizing unit. The activation in fluorescence emission has also been demonstrated in tumor‐bearing nude mice. The glutathione‐responsive behavior has been verified by comparison with the negative results of a non‐cleavable analogue. The results suggest that ferrocenyl BODIPYs could serve as tailorable dark quenchers and the disulfide‐linked phthalocyanine–quencher conjugate acts as an efficient glutathione‐activated photosensitizer for photodynamic therapy. Abstract : Shot in the dark : A near‐infrared‐absorbing ferrocenyl BODIPY dark quencher has been developed and conjugated to a phthalocyanine‐based photosensitizer via a glutathione‐cleavable disulfide linker. The resulting conjugate serves as a glutathione‐activated photosensitizer based on the FRET‐PET mechanism, and the activation has been demonstrated in vitro and in vivo.